Symposium: Redefinitions of Citizenship and Revisions of Cosmopolitanism—Transnational Perspectives - Günter H. Lenz; Rob Kroes; Rüdiger Kunow; Alfred Hornung; William Boelhower (Journal of Transnational American Studies, 2011)
The following set of essays consists of revised versions of contributions read at, or prepared for, a roundtable discussion at the 2009 convention of the American Studies Association in Washington, DC. The short contributions by the individual authors reflect on the boundaries, the perspectives, and the transdisciplinary dynamics of the field imaginary of transnational American Studies and the specific political role of new notions of citizenship and the parameters of a new cosmopolitanism beyond the limits of the Western tradition.